2019
DOI: 10.3390/rs11040413
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Satellite Solar-Induced Fluorescence to Constrain Global Transpiration Estimates

Abstract: The opening and closing of plant stomata regulates the global water, carbon and energy cycles. Biophysical feedbacks on climate are highly dependent on transpiration, which is mediated by vegetation phenology and plant responses to stress conditions. Here, we explore the potential of satellite observations of solar-induced chlorophyll fluorescence (SIF)-normalized by photosynthetically-active radiation (PAR)-to diagnose the ratio of transpiration to potential evaporation ('transpiration efficiency', τ). This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 90 publications
0
40
0
Order By: Relevance
“…SIF emission is related to the light reactions of photosynthesis but GPP estimation also requires information on the dark reactions and stomatal conductance such that the remote sensing community is currently challenged by how to use SIF to estimate GPP. New studies also propose that SIF might be used to monitor T, possibly in combination with surface temperature 10 measurements, acknowledging the close link between GPP and T due to their joint dependence on stomatal conductance and common meteorological and environmental drivers (Alemohammad et al, 2017;Damm et al, 2018;Lu et al, 2018;Pagán et al, 2019;Shan et al, 2019).…”
Section: Solar-induced Fluorescence (Sif)mentioning
confidence: 99%
See 1 more Smart Citation
“…SIF emission is related to the light reactions of photosynthesis but GPP estimation also requires information on the dark reactions and stomatal conductance such that the remote sensing community is currently challenged by how to use SIF to estimate GPP. New studies also propose that SIF might be used to monitor T, possibly in combination with surface temperature 10 measurements, acknowledging the close link between GPP and T due to their joint dependence on stomatal conductance and common meteorological and environmental drivers (Alemohammad et al, 2017;Damm et al, 2018;Lu et al, 2018;Pagán et al, 2019;Shan et al, 2019).…”
Section: Solar-induced Fluorescence (Sif)mentioning
confidence: 99%
“…The authors suggested that the decoupling between GPP and T during water stress episodes hampered the use of SIF to predict T, 20 particularly in grasslands, noting that T can occur without GPP under periods of plant stress (Bunce, 1988;De Kauwe et al, 2019). There is a strong empirical link between the ratio of T over potential evaporation and the ratio of SIF over PAR, and the relationship depends on the atmospheric demand for water, with larger transpiration for the same SIF when potential evaporation is higher Alemohammad et al, 2017;Damm et al, 2018;Lu et al, 2018;Pagán et al, 2019;Shan et al, 2019).…”
Section: Solar-induced Fluorescence (Sif)mentioning
confidence: 99%
“…Recent RS approaches based on measurements of sun-induced chlorophyll fluorescence propose complementary pathways to advance estimates of actual A n (Damm, Erler, & Gioli, 2010;Damm et al, 2015;Mohammed, Colombo, & Middleton, 2019), T (Lu et al, 2018;Pagán, Maes, Gentine, Martes, & Miralles, 2019) and even g s (Shan et al, 2019). Despite the partial success of observational approaches, data scarcity (i.e.…”
mentioning
confidence: 99%
“…SIF emission is related to the light reactions of photosynthesis, but GPP estimation also requires information on the dark reactions and stomatal conductance such that the remote sensing community is currently challenged by how to use SIF to estimate GPP. New studies also propose that SIF might be used to monitor T , possibly in combination with surface temperature measurements, acknowledging the close link between GPP and T due to their joint dependence on stomatal conductance and common meteorological and environmental drivers (Alemohammad et al, 2017;Damm et al, 2018;Lu et al, 2018;Pagán et al, 2019;Shan et al, 2019).…”
Section: Solar-induced Fluorescence (Sif)mentioning
confidence: 99%
“…The authors suggested that the decoupling between GPP and T during water stress hampered the use of SIF to predict T , particularly in grasslands, noting that T can occur without GPP under periods of plant stress (Bunce, 1988;De Kauwe et al, 2019). There is a strong empirical link between the ratio of T over potential evaporation and the ratio of SIF over PAR, and the relationship depends on the atmospheric demand for water, with larger transpiration for the same SIF when potential evaporation is higher (Alemohammad et al, 2017;Damm et al, 2018;Lu et al, 2018;Pagán et al, 2019;Shan et al, 2019). These ratios vary with assumptions regarding the potential evaporation calculation as well (Fisher et al, 2010).…”
Section: Solar-induced Fluorescence (Sif)mentioning
confidence: 99%